Health Diplomacy and Regional Integration in West Africa: The West African Health Organization’s Experience (Journal of International Studies, 2020)
From the outset the founding fathers of Economic Community of West African States (ECOWAS) recognized the relevance of integration in the social sector based on the conviction that intense cooperation in the economic and political sectors alone will not bring about lasting regional integration. For instance, the ECOWAS treaty of 1975 and revised treaty of 1993 had the promotion of social progress and collaboration in the social field as one of the objectives of the community. Yet scholars have not given it the deserved attention. This paper therefore represents an attempt to assess the extent to which the West African Health Organization (WAHO), a specialized health agency of ECOWAS, has contributed to regional health integration in West Africa. It argues that regional integration and cooperation should not be geared solely towards economic and political purposes. It also examines the achievements as well as the major challenges confronting WAHO. It concludes that regional health integration is no longer an option but an imperative for West African countries to meet their common health challenges.